CP-093 Escalation or de-escalation for the treatment of febrile neutropenia. (24th February 2014) - Lenehan, D; Scanlon, N; Brady, D; Dinesh, B; Bergin, S; McWade, R; Lynch, M; Meegan, C
Abstract : Background: Current guidelines at MMUH for the antimicrobial treatment of febrile neutropenia are based on an escalation approach as recommended by the Infectious Diseases Society of America (IDSA) and European Conference on Infections in Leukaemia 3 (ECIL3). Piperacillin/tazobactam in combination with ciprofloxacin or gentamicin are the empiric agents recommended in the current MMUH guidelines. In 2009, a retrospective audit of positive blood cultures from 2006–2008 in MMUH haematology patients with febrile neutropenia was used to assess the appropriateness of the guidelines in use at that time. These guidelines were amended following completion of the audit. With global and national concerns regarding increasing resistance in Gram-negative organisms and considering the new de-escalation approach recently discussed at ECIL4 it was decided to re-audit blood culture results in these patients and assess if any further changes to the local guidelines were necessary. Purpose: To establish the appropriateness of local antimicrobial guidelines for the treatment of febrile neutropenia in MMUH patients. Materials and methods: A retrospective review was undertaken of positive blood culture isolates in haematology patients from July 2009–June 2012. The laboratory information system (Telepath) identified haematology patients. Patients were excluded if they were not neutropenic within 48 h of the positive blood culture. The data collected included the organisms identified and their susceptibility patterns. The current guidelines were then reviewed for appropriateness and will be updated accordingly. Results: An audit with two cycles (2006–2008 and 2009–2012) was completed. Some findings were consistent between the two cycles, e.g. higher bacteraemia rate among patients with profound neutropenia. Levels of susceptibility of Gram-negative organisms to the first-line agent piperacillin/tazobactam were between 79–92% which is reassuring. The main difference noted between the two cycles was a rising quinolone resistance rate to Gram-negative pathogens over time. Conclusions: The MMUH guidelines for the antimicrobial treatment of febrile neutropenia require modification to reflect quinolone resistance. This re-audit reassures us that empiric piperacillin/tazobactam in combination with gentamicin remains a satisfactory first line treatment in these patients. Currently, there is no indication for such a radical approach as the de-escalation approach discussed at ECIL 4. No conflict of interest.